Quality control improvement at Jana DCS Sdn. Bhd. - Abd Wahab, Muhammad Badrul Amin; Mustar, Muhamad Radzi; Mohamad Rus, Mohamad Arif; Mahmood, Salwa; Raja Mamat, Tengku Nur Azila (Penerbit UTHM, 2020)
Jana DCS Sdn. Bhd. is one of the companies that run the service of air conditioning system supply in Nusajaya, Johor, Malaysia. Quality improvement is one of the most important part when talking about a company, mostly companies that operate in service industries. Quality control plays the major parts in quality improvement as quality control is an operational technique to ensure efficient and effective operation. Roughly, total net area cooled by Jana DCS Sdn. Bhd. is 590,000 square feet as for Johor State Government Administration Centre. While for Puteri Harbour, the total net area cooled is 614,000 square feet. Jana DCS Sdn. Bhd. operates Iskandar Malaysia’s first district cooling plant, with both thermal energy and chilled water storage capability that produce and supply cooling load for air conditioning to the Johor State Government Complex at Kota Iskandar and to various private sector developments at Puteri Harbour.